Implications of Self-Efficacy in Guidance Personal and Social Independence - Munawati, Siti; Rahmatullah, M Asep; Manan, Abdul (Jurnal Pendidikan Ilmu Sosial, 2022)
ABSTRACTSinar Cendekia (SC) is an educational institution that is managed professionally, from creative-innovative learning strategies and organized teacher and student development models. This study uses a qualitative methodological approach, namely a research method based on the post-positivism philosophy, which is used to examine the condition of a natural object, where the researcher is the key instrument, the data collection technique is done in a triangulation (combined), qualitative data analysis. The types and sources of data collected in this study are primary data sources, from data and information from interviews, observations and documentary studies found. This study sees that the implication process of self-efficacy is to be able to deal with one's own inner state, to regulate itself in spirituality, physical care, and in fostering human relationships with others in various environments through individual / group research activities in the form of visits to certain places that reflect one regional development dynamics.